Numerical and experimental investigation of heat transfer in a dimpled and petaled array tube with a coiled twisted tape and SiC nanofluid - Hariam Luqman Azeez; Adnan Ibrahim; Banw Omer Ahmed; Sharul Sham Dol; Ali H.A. Al-Waeli; Mahmoud Jaber (Case Studies in Thermal Engineering)
Thermal efficiency challenges are common in absorber tube designs. This study proposes an innovative absorber tube featuring dimples and petal arrays on its surface, integrated with a coiled twisted tape, and circulating a 0.9 % volume concentration of silicon carbide (SiC)-enhanced nanofluid. Fixing heat flux at 1000 W/m2 and Reynold number between 720 and 5030, Computational Fluid Dynamics (CFD) was employed to optimize key dimple parameters, encompassing dimple lines number (ranging from 2 to 6), dimple diameter (1–5 mm), dimple height (0.8–2 mm), and dimple pitch distance (10–30 mm). Additionally, Thermohydraulic Performance Factor (THPF) assessment was conducted experimentally to examine the impact of petal arrays, coil, twisted tape, and three concentrations of SiC-enhanced nanofluid on the optimized dimple tube. The results indicate that a configuration with five dimple lines, a dimple diameter of 3 mm, a dimple height of 1.4 mm, and a dimple pitch distance of 10 mm provides optimal heat transfer augmentation. Furthermore, incorporating 0.9 % SiC with a coiled twisted tape into the optimized dimpled and petaled array tube design enhances the THPF by 71.1 %, demonstrating a substantial improvement in thermohydraulic performance.